Dynamic Macrophages: Understanding Mechanisms of Activation as Guide to Therapy for Atherosclerotic Vascular Disease - Decano, Julius L.; Aikawa, Masanori (Frontiers in Cardiovascular Medicine, 2018)
Macrophages in atherosclerosis are both malleable and heterogeneous. They are dynamic in that they can switch phenotypes in response to the environmental signals, from plasma lipid levels, to T cell interactions and their own metabolic states to either advance or suppress vascular inflammation. Their importance in coronary arterial disease (CAD) is underscored by the fact that despite reduction of major risk factors like LDL cholesterol levels, some patients remain at high risk related major adverse cardiovascular events (MACE) due to a prominent inflammatory status. Emerging evidence suggests that metabolic reprogramming of macrophages can trigger either a pro-inflammatory or anti-inflammatory behavior. Warburg-like phenomenon is seen in pro-inflammatory macrophages, while non/anti-inflammatory macrophages tend to rely on OXPHOS and have a better mitochondrial fitness. Lipids can induce changes in macrophage activation with cholesterol crystals triggering inflammasome-mediated cascade of activation while specialized pro-resolving mediators (SPMs) promote resolution of inflammation. T cells can also influence macrophage activation beyond paracrine signaling through molecular interactions of immune checkpoint proteins that either co-stimulate or co-inhibit activation. More pathways of activation can be uncovered by inspecting macrophages in the single cell level since differential changes in key gene regulators can be screened in higher resolution compared to conventional averaged gene expression readouts. All these mechanisms of macrophage activation can simultaneously be expanded and consolidated by using approaches in network biology. Such integration of disparate information can unravel novel and potentially safer drug targets though better understanding of the pro-inflammatory activation circuitry. □